Pengaruh DER, TAO, dan CR Terhadap Pertumbuhan Laba - Sri Ayem; Uum Helmina Chaerunisak; Melkianus Marawali (Jurnal Literasi Akuntansi, 2024)
This study aims to examine the effect of Debt Equity Ratio, Total Assets Turn Over, Current Ratio on Profit Growth. This study uses a sample of manufacturing companies in the Food and Beverage sector which are listed on the Indonesia Stock Exchange. The type of data used in this research is the secondary data of the company's financial statements. During the 2018 – 2021 period, there were 12 registered Food and Beverage companies. The sampling method used in this study was purposive sampling, namely the sampling method determined by the researcher based on certain criteria. Manufacturing companies taken based on the researchers' criteria are 4 sample companies. The data analysis method used consists of descriptive statistical tests, classical assumption tests, multiple linear regression analysis, t tests, f tests and determination tests (R2) using the test tool (SPSS) version 25. The results of this study include (1) Debt Equity Ratio has a positive effect on Profit Growth, (2) Total Assets Turn Over has a positive effect on Profit Growth, (3) Current Ratio has a negative effect on Profit Growth. Keywords: Debt Equity Ratio, Total Assets Turn Over, Current Ratio, Profit Growth.